Employee’s Perception of Organizational Politics and its Relationship with Turnover Intention - Chukwu, B.A.; Chukwu, B.A.; Aguwamba, S.M.; Ezeabogu, A.N. (International Journal of Economics, Business and Management Studies, 2019)
This research investigated employee perception of organizational politics and its relationship with turnover intention in Public/Private Organization in Nigeria. Various literature in organizational politics revealed that turnover intention is an inevitable outcome. Employees will intend to leave when there is unjust appraisal system, pay and promotion policies emanating from manipulation through politics. Performance appraisal processes in organization is often political in nature especially when it involves promotion. The data for this research was collected from Primary source. Survey research method was utilized to collect Primary data. Sample size of 90 employees from Public/Private organizations in Enugu State, Nigeria was collected. Simple regression and Pearson correlation was used to test hypothesis. The simple regression result indicated that perception of organizational politics had positive and significant relationship with turnover intention at 5% level of significance. Pearson correlation result for perception of organizational politics and turnover intention (r = 0.371<0.05) indicated that positive association exists between perception of organization politics and turnover intention. The positive coefficient means that the increase in perception of organizational politics might lead to increase in turnover intention. The study recommended that management of organizations should discourage politically manipulative behavior and ensure Justice in performance evaluation.